Evaluation of the usefulness of a paper-pencil group cognitive assessment for older adults in the community - Daisuke Cho; Hiroyuki Suzuki; Susumu Ogawa; Tomoya Takahashi; Kenichiro Sato; Ai Iizuka; Momoko Kobayashi; Misako Yamauchi; Anna Kinai; Yan Li; Yoshinori Fujiwara (BMC, 2023)
Abstract Background As the older population increases, the need for early detection of cognitive decline is also increasing. In this study, we examined whether our paper-pencil type group examination for cognitive assessment (PAPLICA) could detect the effects of years of education and aging. Methods PAPLICA was conducted on 829 older people. The inclusion criteria were age 60 years or older and the ability to come to the event site alone. The exclusion criteria were participants with a medical or psychiatric disorder or dementia.One examiner conducted the test on a group of approximately 10-20 people in approximately 25 min. Participants were instructed on tackling the issues projected on the projector, and their answers were recorded in a response booklet. Results An independent sample t-test was performed for years of education, and ANCOVA was performed for aging. Among the test items included in PAPLICA, the Speed I and Letter fluency tests were unable to detect the effects of aging. Furthermore, the age at which the effect of aging manifests varies depending on the test item. For instance, a decline in scores in the Speed I and Picture ECR Free recall tests was observed in the 70-74 age group; for that of Word DRT, Picture ECR cued recall, and Similarity, in the 75-79 age group; for CFT, in the 80-84 age group, and for CLOX, the decline was observed in the 85 ≤ age group. Conclusions PAPLICA, similar to other neuropsychological tests, was able to detect the effects of years of education and aging. Future testing should be conducted on different demographics to identify the differences in patterns of cognitive decline.